Green Sukuk dan Kepatuhan Syariah: Penguatan Kerangka Hukum Verifikasi Proyek Berkelanjutan di Indonesia - Nisa Afifah; Gicella Sonbay; Defrianus Nong Deris; Bimaryudho Dhimas Kurnia Armadha; Mujiburrohman Mujiburrohman; Muhamad Abdul Kholik (Syariah: Jurnal Hukum dan Pemikiran, 2026)
Indonesia’s green sukuk has been widely promoted as an innovation in sustainable Islamic finance. However, behind this development remain structural problems related to regulatory fragmentation, verification gaps, and the risk of greenwashing that threaten legal certainty, accountability, and investor confidence. Amid growing international debates on sustainable finance regulation, Islamic financial governance, and sharia-based environmental accountability, there is still no legal framework that operationally integrates maqāṣid al-sharī‘ah principles with measurable sustainability verification mechanisms. This study examines three main issues, namely the conceptualization of green sukuk within sharia business law, the weaknesses of environmental sharia verification mechanisms in Indonesia, and the formulation of an ideal legal framework capable of ensuring measurable dual compliance between environmental sustainability and sharia principles. The research employs a normative juridical method using conceptual and comparative approaches through the analysis of the Sovereign Sukuk Law, Financial Services Authority Regulation Number 18 of 2015, DSN-MUI Fatwa Number 122 of 2018, the Indonesian Green Sukuk Framework, and comparative practices in Malaysia and the United Kingdom. The findings demonstrate that the current legal framework only establishes formal conformity between green sukuk and sharia principles without operationalizing maqāṣid al-sharī‘ah as technical evaluative indicators. The system also maintains a separation between sharia audits and environmental audits and lacks a national institution responsible for coordinating environmental sharia verification, thereby creating opportunities for greenwashing practices. In response, this study proposes the establishment of the National Green Sharia Audit Board and the National Standard for Green Sukuk Sharia Verification as mechanisms for translating maqāṣid al-sharī‘ah into substantive dual compliance indicators. The study contributes to the development of Islamic financial law by shifting the paradigm from formal normative compliance toward substantive and functional compliance within sustainable Islamic finance governance.